Acto de Juramentación. (UNED, 2024)
Aparece de izquierda a derecha, Ana Patricia Cascante Monge (de saco rosado), Ana Lorena Carvajal Pérez, Luis Guillermo Carpio Malavassi y Grace Alfaro Alpízar; sentados en el mismo orden aparece Flor Eugenia Chaves Hidalgo, Jhonny Valverde Chavarría y Viviana Pacheco